Biological characteristics of ethnobotanical study of medicinal plants used by Donggo Ele tribe in Wawo District, West Nusa Tenggara Province - Saribanon, Nonon; Adilah, Hanifa; Prasasty, Vivitri; Sinaga, Ernawati (Ethnobotany Research and Applications, 2026)
Background: Medicinal plants represent invaluable natural resources sustained through indigenous traditional knowledge systems. This ethnobotanical investigation examined medicinal plant knowledge of the Donggo Ele tribe in Wawo District, Bima Regency, West Nusa Tenggara Province, Indonesia. Methods: Data collection employed semi-structured interviews with 70 informants including traditional healers (Sando) and village elders, selected through purposive and snowball sampling. Plant specimens were identified through field surveys and taxonomic references. Quantitative ethnobotanical indices including Relative Frequency of Citation (RFC), Species Use Value (SUV), Family Importance Value (FIV), Fidelity Level (FL), and Plant Part Value (PPV) were calculated. Results: The study documented 171 medicinal plant species from 62 families utilized for treating 67 different ailments. Curcuma longa L. was the most frequently cited species (RFC 69.048%), while Zingiberaceae demonstrated the highest Family Importance Value (90.476%). Abrus precatorius and Gomphrena globosa exhibited the highest Species Use Values (4.50 and 4.00, respectively). Syzygium aqueum showed perfect Fidelity Level (100%) for treating gastrointestinal disorders. Leaves constituted the most utilized plant parts (PPV 38.082%), with preparation methods primarily involving pounding and boiling (34%), and oral administration being preferred (58.3%). Conclusions: The Donggo Ele community maintains extensive traditional medicinal plant knowledge actively integrated into healthcare practices. However, this knowledge faces threats from modernization and disrupted intergenerational transmission. Comprehensive documentation efforts, community-based conservation initiatives, and sustainable utilization strategies are essential for preserving this biocultural heritage while exploring potential contributions to pharmaceutical research. Keywords: Ethnobotany; Traditional medicine, Quantitative indices; Biocultural conservation, Donggo Ele